2019
DOI: 10.1029/2019jd030507
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of the Irrigation Effects on Surface Fluxes and Local Climate in Typical Mountain‐Oasis‐Desert Systems in the Central Asia Arid Area

Abstract: In this study, the Weather Research and Forecasting model was coupled with an improved Noah land surface model (WRF‐Noah) where dynamic flood and drip irrigation processes were implemented firstly. We simulated the different irrigation effects on surface water‐heat processes in a typical mountain‐oasis‐desert system in Central Asia for both wet and drought years, respectively, using the modified WRF‐Noah. The modified WRF‐Noah model can dynamically generate amounts of irrigation in agreement with actual values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 86 publications
5
32
0
Order By: Relevance
“…Other studies have also shown that the use of flood irrigation and drip irrigation in oases in the arid region of Central Asia increases the water vapor in the air and accelerates the hydrological cycle of the whole region. However, due to the existence of local circulation (the role of valley winds), summer precipitation in mountainous areas increased significantly, but there was no obvious trend of wetting in the deserts and oases [33].…”
Section: Pronounced Warming and Drying Trends In Oasesmentioning
confidence: 99%
“…Other studies have also shown that the use of flood irrigation and drip irrigation in oases in the arid region of Central Asia increases the water vapor in the air and accelerates the hydrological cycle of the whole region. However, due to the existence of local circulation (the role of valley winds), summer precipitation in mountainous areas increased significantly, but there was no obvious trend of wetting in the deserts and oases [33].…”
Section: Pronounced Warming and Drying Trends In Oasesmentioning
confidence: 99%
“…Finally, since the 1950s, the intensified agriculture activities and widespread use of irrigation have significant impact on the regional water‐heat budget, consumed water measuring about 10,000 m 3 ha −1 in farmland and accordingly increasing the local evapotranspiration, which may induce the nonclosure of the surface energy balance in this region (Zhang et al., 2019). In this study, because of the limitation of observed surface energy fluxes, we only validated the model performance in natural vegetation without irrigation and further verification is needed in irrigation‐intensified oasis in order to improve the model's ability in simulating fluxes (Amri et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Being one of the driest regions in the world, Central Asia is not only more sensitive to global climate change, but also have been largely affected by regional anthropogenic influence, such as the development of irrigated agricultural (Mirzabaev et al., 2016; Zhang et al., 2019). Especially in Aral Sea region, large irrigation systems were created by the former Soviet Union to divert water from the Amu Darya and Syr Darya rivers in order to promote agriculture production (Lioubimtseva et al., 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The northern slope of the Tien Shan Mountains belongs to a typical mountain-oasisdesert (from high land to low land) ecosystem [2,3] in the arid regions of Central Asia. The distribution of flora and fauna is strongly dependent on elevation variation.…”
Section: Introductionmentioning
confidence: 99%
“…Our objective is to examine the relationship between RHD and ecosystems across elevation gradients and to determine their corresponding mechanisms when RHD and local conditions are influenced by the same environmental factors. This is particularly important to examine within NTXJ because local climate patterns have changed significantly [3], and precipitation in the mid-mountain region has increased due to oasis expansion and increased irrigation [27]. Thus, furthermore, the distribution and intensity of grazing may also be influenced by climate change and vegetation dynamics [28].…”
Section: Introductionmentioning
confidence: 99%